(untitled) (Eurasian Research Bulletin, 2023)
Declaration of assets and income of public officials is an important tool for ensuring transparency and accountability in governance. It is widely recognized that public officials should declare their assets and income to prevent corruption, conflicts of interest, and illicit enrichment. In recent years, many countries have introduced mandatory asset and income declaration requirements for public officials. The literature on the topic suggests that effective implementation of asset and income declaration requirements can contribute to improving the integrity of public officials and reducing corruption. However, the implementation of such requirements faces a number of challenges, including lack of political will, inadequate legal framework, inadequate enforcement mechanisms, and lack of public awareness and participation. International experience shows that the success of asset and income declaration systems depends on a number of factors, such as the clarity of legal provisions, the scope and coverage of the requirements, the accuracy and reliability of the data collected, the accessibility of the information to the public, and the effectiveness of enforcement mechanisms. Successful implementation of asset and income declaration requirements also requires strong political commitment, adequate resources, and public support. In conclusion, the analysis of international experience suggests that effective implementation of asset and income declaration requirements is an important tool for promoting transparency and accountability in governance. However, the success of such requirements depends on a range of factors, including legal framework, enforcement mechanisms, public awareness and participation, and political commitment